Moral Panic About Refugees in Poland as a Manifestation of Cultural Transformation - Pasamonik, Barbara (Zakład Edukacji Międzykulturowej i Badań nad Wsparciem Społecznym Wydziału Nauk Historycznych i Pedagogicznych Uniwersytetu Wrocławskiego, 2017)
The mass exodus of refugees from the Middle East and North African countries in 2015 as well as the pictures of migrants storming the European Union borders provoked moral panic in many European countries, not excluding Poland. The Polish transformational panic about refugees is part of a broader culture war within the West – a clash of traditionalism and modernism, conservatism and liberalism of lifestyle, moral fundamentalism and relativism.
Keywords: culture war; migrant crisis; moral panic; refugees; transformational panic